Teledentistry as potential opportunity for the improvement of dental are in periods of social isolation: preliminary results of literature review - Gebczynski, Krzysztof A.; Zarzecka, Joanna; Słowik, Joanna (Journal of Stomatology, 2020)
The literature on teledentistry and telemedicine was reviewed in the PubMed (302) and Embase (131) bases, using following keywords and their combinations: “iPad”, “tablet”, “cell phone”, “smartphone”, “mouth hygiene”, “oral hygiene”, “dental hygiene”, “mouth care”, “mouth washing”, “mouth rinsing”, “tooth hygiene”, “oral health”, “mobile applications”, “app”, “mobile app”, “teledentistry”, “telemedicine”. Non-English written articles and those published before 1995 were excluded from the review. Forms of remote contact in conditions of social isolation may prove to be among the most effective methods supporting medical care for patients. Telemedicine is a multidimensional concept, signifying the provision of medical services (healthcare) and medical education as well as conducting scientific research, using telecommunication and IT tools. The COVID-19 pandemic has presented unprecedented challenges at every level of public life, including that of ensuring the safety of medical care. Dentists, in their daily practice, are among the most vulnerable professional groups. During the pandemic period, in addition to many restrictions regarding the provision of health services, teleconsultation prior to admission of the patient to the dental surgery is recommended. In a condition of social isolation, archived or real-time as well as radiographic images of clinical status would greatly facilitate the correct diagnosis and monitoring of the treatment process. Additionally, these images enable training of medical staff, implementation of pre- and post-graduate curricula, and conducting scientific research.